A Study On Corporate Governance And Performance Effect Of Institutional Investors - Cheng Min (European Scientific Journal, ESJ, 2016)
Recently with rapid growth of China's institutional investors, they are gradually becoming the dominant force in capital market. At the same time they start exerting influence on corporate governance and affecting corporate performance. Many previous studies have shown institutional investors’ holdings are positively correlated to corporate performance. However there are still many studies holding opposite opinions. This article further studies how institutional investors influence corporate performance and whether they have effects on corporate governance. On the whole, we come to the conclusion that participation of institutional investors promotes the improvement of corporate performance. These conclusions provide theoretical and practical guidance to future development of institutional investors.